Clinical and Laboratory Characteristics and Associated Factors to Mortality in Neonates with Birth Asphyxia: A Prospective Observational Study - Nguyen, Thi Thanh Binh; Vu, Thi Dieu Huong; Tran, Binh Thang (Tạp chí Y Dược Huế, 2023)
Aims: To describe the clinical and laboratory characteristics and to investigate associated factors with mortality of birth asphyxia. Methods: This was a prospective observational study conducted on a total of 120 asphyxiated neonates admitted to the Neonatal Intensive Care Unit (NICU). Results: Severe asphyxia was observed in 33.3%, and moderate asphyxia in 66.7% of the cases. The mortality rate was 19.2%. The common clinical features: apnea/gasping (45.8%), hypothermia (37.5%), lethargy (33.0%). The serious clinical signs: abnormal heart rate (15.8%), gastrointestinal bleeding (13.3%), oliguria and anuria (17.5%). The laboratory findings showed hypoglycemia (30.8%), elevated SGOT (45.0%), serum creatinine > 133 µmol/l (31.7%), hyponatremia (35.0%), hypocalcemia (65.8%), elevated lactate > 5mmol/l (53.6%). The factors that increased the risk of mortality in neonatal asphyxia were Apgar score at 5 min ≤ 5, seizure/coma, need for mechanical ventilation, serum creatinine > 133 µmol/l, liver injury, and lactate ≥ 5 mmol/l. Conclusion: The mortality rate is still high, and elevated serum creatinine, elevated liver enzymes, elevated lactate, and low 5-minute Apgar scores increase the risk of death in asphyxiated neonates.